Experimental Identification of Characteristic Curves of Supersonic Vacuum Ejector and Empirical Prediction of Total Evacuation Time - Llorenç Macia; Robert Castilla; Gustavo Raush; Pedro Javier Gamez-Montero (Applied Sciences)
Supersonic vacuum generators, or ejectors, operate pneumatically to extract air from tanks in industrial applications. A key performance metric for ejectors is the Total Evacuation Time (TET), which measures the time required to reach minimum pressure. This research predicts TET using empirical models that rely on two key metrics: the characteristic curve, which relates absorbed flow rate to the working pressure, and the polytropic curve, which describes the evolution of the polytropic coefficient across working pressures. Accurately capturing both curves for subsequent fitting to polynomial curves is crucial for forecasting TET. Several experimental setups were employed to capture the curves, each of which refined the data and improved the quality of the polynomial fits and coefficients. Multiple setups were necessary to pinpoint the breakpoint, from supersonic to subsonic operation mode, which is a critical factor that affects the characteristic curve and the TET. Furthermore, the research shows an improvement in the TET forecasts for each setup, with deviations between experimental and predicted TET ranging from 7.6% (14.5 s) to a 1.4% (2.6 s) in the most precise setup. Once the models were validated, an optimized ejector design, extracted from an author’s previous article, was tested. It revealed a 4% improvement (8 s) in the TET. These results highlight the importance of the mathematical models developed, which can be used in the future to compare ejectors and reduce the need for experimental data.